Fenestrated Stent Graft Repair of Abdominal Aortic Aneurysm: Hemodynamic Analysis of the Effect of Fenestrated Stents on the Renal Arteries - Zhonghua Sun; Thanapong Chaichana (My University, 2009)
Objective:We wanted to investigate the hemodynamic effect of fenestrated stents on the renal arteries with using a fluid structure interaction method.Materials and Methods: Two representative patients who each had abdominal aortic aneurysm that was treated with fenestrated stent grafts were selected for the study.3D realistic aorta models for the main artery branches and aneurysm were generated based on the multislice CT scans from two patients with different aortic geometries.The simulated fenestrated stents were designed and modelled based on the 3D intraluminal appearance, and these were placed inside the renal artery with an intra-aortic protrusion of 5.0-7.0 mm to reflect the actual patients' treatment.The stent wire thickness was simulated with a diameter of 0.4 mm and hemodynamic analysis was performed at different cardiac cycles.Results: Our results showed that the effect of the fenestrated stent wires on the renal blood flow was minimal because the flow velocity was not significantly affected when compared to that calculated at pre-stent graft implantation, and this was despite the presence of recirculation patterns at the proximal part of the renal arteries.The wall pressure was found to be significantly decreased after fenestration, yet no significant change of the wall shear stress was noticed at post-fenestration, although the wall shear stress was shown to decrease slightly at the proximal aneurysm necks. Conclusion:Our analysis demonstrates that the hemodynamic effect of fenestrated renal stents on the renal arteries is insignificant.Further studies are needed to investigate the effect of different lengths of stent protrusion with variable stent thicknesses on the renal blood flow, and this is valuable for understanding the long-term outcomes of fenestrated repair.ndovascular aneurysm repair (EVAR) is now recognised as an effective alternative to conventional open surgery for treating patients with abdominal aortic aneurysm (AAA) since it was first introduced into the clinical practice in 1991 (1, 2).Since then, many patients have been treated with different endovascular devices, including transrenal/suprarenal fixation, to enhance the stability in the proximal aneurysm neck (3-6).However, there are still a significant number of patients who remain unsuitable for such techniques because of their unfavorable aortic anatomy.The main limitation to successful EVAR is the presence of an unsuitable infrarenal aortic neck, which mainly includes a short (< 10 mm) or angulated proximal neck (> 60。 ), and the presence of thrombus/atheroma or severe calcification in the neck (7, 8).The above problems limit endovascular repair of an AAA and these problems can be solved by using a customized designed fenestration stent-graft.Using a customized
Keywords: Fenestration; Abdominal aorta; Aortic aneurysm repair treatments